CT-proAVP IS NOT A GOOD PREDICTOR OF VASOPRESSOR NEED IN SEPTIC SHOCK. Issue 4 (October 2015) - Laribi, Said; Lienart, Daphné; Castanares-Zapatero, Diego; Collienne, Christine; Wittebole, Xavier; Laterre, Pierre-François
ABSTRACT: Introduction: Septic shock features a high hospital mortality. Improving our ability to risk stratify these patients at admission may help better define management strategies and design studies. The primary objective of this study was to determine if patients dead or with sustained vasopressor need at day 7 had a relative arginine vasopressin (AVP) deficiency as compared with vasopressor-free patients at day 7. Another objective was to explore if plasma CT-proAVP (C terminal part of preprovasopressin) measured within 24 h of sepsis onset could predict patient severity. Methods: This was a prospective observational study in a medical and surgical intensive care unit. One hundred thirteen patients were included in this analysis: 102 patients with severe sepsis or septic shock and 11 nonseptic controls. The CT-proAVP was measured at three time points within the first week after sepsis onset. Results: The CT-proAVP measured within 24 h of sepsis onset failed to predict vasopressor need. More importantly, CT-proAVP plasma levels in patients with a sustained need of vasopressors did not differ from vasopressor-free patients at days 1 and 2. The CT-proAVP was more elevated in septic shock as compared with severe sepsis or nonseptic patients. When analyzing 28-day mortality, nonsurvivors featured higher levels of the CT-proAVP compared with survivors. Conclusions: Patients with septic shock and sustained need of vasopressors do not seem to present a relative AVP deficiency. In sepsis, the subgroup of patients that may benefit from AVP supplementation still needs to be identified. Our study further confirms previous data on the ability of the CT-proAVP to predict patient severity in severe sepsis and septic shock. Abstract : Supplemental Digital Content is available in the text